A guideline on constructing multivariate control chart using excel spreadsheet / Siti Rahayu Mohd Hashim and Norazah Abu Bakar - Mohd Hashim, Siti Rahayu; Abu Bakar, Norazah (2008)
Multivariate process control chart (MSPC) is the most popular method in statistical process control which involves more than one quality characteristic. It is much simpler if the process has only one quality characteristic. If there are several quality characteristics involved, a specific and costly statistical programming package is needed to assist the construction of the multivariate control chart. This poster presentation will put researchers and the users of MSPC at ease by providing a step by step guideline using EXCEL spreadsheet for that purpose. This guideline will enable any interested researchers to write the language programming on constructing multivariate process control chart.